The curse of the mummy's tomb - Stine, R. L. (New York : Scholastic, 1993)
Lost in an Egyptian pyramid, twelve-year-old Gabe and his cousin Sari find they are not alone.
"An Apple paperback."
Elem. School Library Collection
4.9
5-8
Keywords: Mummies -- Fiction; Pyramids -- Fiction; Horror stories; Mummies -- Fiction; Pyramids -- Fiction; Horror fiction